Textbook of practical geography # Text book of practical geography - Singh, Rana P. B.; Khan, Zulfequar. Ahmad; Khan,Zulfequar.Ahmad (New Delhi # Ludhiana Kalyani Publishers # Concept Publishing Company, 1998)
Scales